Peran Guru sebagai Pemimpin dalam Pembelajaran Paud yang Efektif - Nur Ramida; Habibah Habibah; Nur Sa’adah; Margaretha Kurnia Sari; Aslamiah Aslamiah; Celia Cinantya (Asosiasi Periset Bahasa Sastra Indonesia, 2025)
The role of the teacher as a leader in PAUD learning is very important to create an effective and quality learning process. Teachers not only function as teachers, but also as leaders who direct, motivate and create a learning environment conducive to children's cognitive, social and emotional development. Through experiential and game-based learning approaches, teachers are able to develop independence and leadership skills in students from an early age. In addition, teachers also act as facilitators, motivators, and inspirers who provide examples and support to optimize children's potential. Teacher leadership in PAUD is essential to improving the quality of learning and shaping children's character as a whole.